Metal-based combinations that target protein synthesis by fungi - Vallières, Cindy; Avery, Simon V. (Elsevier, 2017)
A wide range of fungicides (or antifungals) are used in agriculture and medicine, with activities against a spectrum of fungal pathogens. Unfortunately, the evolution of fungicide resistance has become a major issue. Therefore, there is an urgent need for new antifungal treatments. Certain metals have been used for decades as efficient fungicides in agriculture. However, concerns over metal toxicity have escalated over this time. Recent studies have revealed that metals like copper and chromate can impair functions required for the fidelity of protein synthesis in fungi. This occurs through different mechanisms, based on targeting of iron–sulphur cluster integrity or competition for uptake with amino acid precursors. Moreover, chromate at least acts synergistically with other agents known to target translation fidelity, like aminoglycoside antibiotics, causing dramatic and selective growth inhibition of several fungal pathogens of humans and plants. As such synergy allows the application of decreased amounts of metals for effective inhibition, it lessens concerns about nonspecific toxicity and opens new possibilities for metal applications in combinatorial fungicides targeting protein synthesis.